A new case of intragenic deletion of the TCF4 gene without features of Pitt-Hopkins syndrome - Morožin Pohovski, Leona (Array, 2020)
Different genomic alterations affecting the TCF4 gene are usually associated with Pitt-Hopkins syndrome (PTHS). This syndrome is a rare neurodevelopmental genetic disorder characterized by distinctive facial features, abnormal breathing, psychomotor delay and severe intellectual disability (ID). The genomic alterations include whole or partial gene deletion; balanced translocation disrupting the coding sequence of the gene; and intragenic variants. The TCF4 gene encodes a basic helix-loop-helix (bHLH) transcription factor 4. Using alternative promoters, TCF4 can be transcribed from a number of alternative initial exons, allowing for translation of variable protein isoforms containing different functional domains. Full-length TCF4 has two activation domains (AD1 and AD2) that are thought to modulate transcriptional activity, a NLS domain (nuclear localization signal) that controls subcellular localization and bHLH domain. Typical PTHS patients have aberration localized between exons 9 and 18 of the gene. On the other hand, variants affecting the first protein coding exons give rise to mild non-syndromic ID. We present a ten-year-old girl with psychomotor delay and mild ID without the typical features of PTHS. Genetic investigation using array-based comparative genomic hybridization, revealed a 73.45 kb deletion within the TCF4 gene. The deletion encompassing only exon 6 (NM_001083962). This deletion was not detected in both parents. Cytogenetic analysis excluded balanced translocation disrupting the coding sequence of the gene. To the best of our knowledge, this is the first case described in literature involving only exon 6. The findings in our patients support the notion that position of the alteration in TCF4 is relevant to the phenotype. Reporting our case we want to contribute to the phenotype-genotype correlation in patients with intragenomic deletion of TCF4 gene.